Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1089/jmf.2014.3341
|View full text |Cite
|
Sign up to set email alerts
|

Lonicera japonicaTHUNB. Extract Inhibits Lipopolysaccharide-Stimulated Inflammatory Responses by Suppressing NF-κB Signaling in BV-2 Microglial Cells

Abstract: In the current study, we evaluated the anti-inflammatory effects of Lonicera japonica THUNB. (LJ) and its underlying molecular mechanism in lipopolysaccharide (LPS)-stimulated BV-2 microglial cells. Our results indicated that LJ significantly inhibits LPS-stimulated production of nitric oxide (NO) and prostaglandin E2 (PGE2). In addition, LJ inhibited inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) at both the protein and mRNA levels. In LPSstimulated BV-2 microglial cells, LJ inhibited pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…For in vitro studies, the mouse microglial BV‐2 cell line was obtained from Professor Choon‐gon Jang of the School of Pharmacy at Sungkyunkwan University . BV2 cells were cultured in Dulbecco's modified Eagle's medium (Gibco) containing 10% heat‐inactivated fetal bovine serum (30‐2020, ATCC) and antibiotics (100 μg/mL streptomycin and 100 IU/mL penicillin, Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…For in vitro studies, the mouse microglial BV‐2 cell line was obtained from Professor Choon‐gon Jang of the School of Pharmacy at Sungkyunkwan University . BV2 cells were cultured in Dulbecco's modified Eagle's medium (Gibco) containing 10% heat‐inactivated fetal bovine serum (30‐2020, ATCC) and antibiotics (100 μg/mL streptomycin and 100 IU/mL penicillin, Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…LPS activates innate immune cells, which leads to the production of pro-inflammatory cytokines (22). It has been reported that citrate is able to modulate LPS-induced monocyte inflammatory responses (23) and that suppression of NF-κB signaling in BV-2 microglial cells inhibits LPS-induced inflammatory responses (24). The present study demonstrated that LPS treatment significantly increased the release of inflammatory cytokines TNF-α and IL-1β, which indicated that LPS was able to induce the inflammatory response in NK92 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse microglial cell line, BV-2, was kindly provided by Prof. Choon-gon Jang at Sungkyunkwan University [ 49 ]. The rat glioma cell line (C6) was obtained from American Type Culture Collection (Manassas, Virginia, USA).…”
Section: Methodsmentioning
confidence: 99%